Structural Characterization and Infrared and Electrical Properties of the New Inorganic-Organic Hybrid Compound - A. Oueslati; I. Chaabane; K. Adil; F. Hlel (Journal of Chemistry)
New inorganic-organic hybrid [(C3H7)4N]2Hg2Cl6 compound was obtained and characterised by single-crystal X-ray diffraction, infrared, and impedance spectroscopy. The latter crystallizes in the monoclinic system (space group C 2/c, ) with the following unit cell dimensions: (1) Å, (6) Å, (2) Å, and (2). Besides, its structure was solved using 84860 independent reflections leading to . Electrical properties of the material were studied using impedance spectroscopic technique at different temperatures in the frequency range of 209 Hz to 5 MHz. Detailed analysis of the impedance spectrum suggested that the electrical properties of the material are strongly temperature-dependent. The Nyquist plots clearly showed the presence of bulk and grain boundary effect in the compound.